Measurement placement for power system state estimation by decomposition technique - Rakpenthai C. (2014)
This paper presents the concept of distributed process to improve the previously proposed measurement placement method for power system state estimation in which the minimum condition number of the measurement matrix is used as a criterion in conjunction with sequential elimination to reach the near optimal measurement placement. Firstly, the entire network of the power system is decomposed into smaller subsystems. Then, in each subsystem, the optimal positions for measurement placement are determined by using the minimum condition number criteria. The numerical experiment results on the IEEE 14-bus system indicate that the proposed technique gives the measurement matrix with smaller condition number and the computation time is much shorter. ©2004 IEEE.